Analisis Elastisitas Permintaan Minyak Goreng Di kabupaten Rokan Hulu - Rini; Laily Fitriana; Sischa Febriani Yamesa Away (Universitas Pasir Pengaraian, 2023)
The food needs of each region can be influenced by various factors, one of the products that has high demand is cooking oil, in the last five years, cooking oil is one of the staple foods needed by the people in Rokan Hulu district. The amount of demand for cooking oil can be measured based on the elasticity of demand for the product. This study aims to determine the factors that affect the elasticity of cooking oil demand in Rokan Hulu district and measure the value of cooking oil demand elasticity in Rokan Hulu. The research method uses the quantitative method with multiple linear regression analysis and elasticity analysis, the data used is secondary data.The results of this study show that 1) The factors that affect the demand for cooking oil in Rokan Hulu district are partially variable bulk oil prices, per capita income and population, while the variables of packaged oil prices and egg prices have no influence on cooking oil demand in Rokan Hulu district. Simultaneously, all variables have an influence on the demand for cooking oil in Rokan Hulu district. The value of determination shows that 99.6% of oil demand is influenced by all independent variables2) The elasticity of demand for cooking oil in Rokan Hulu district consists of price elasticity, namely the price of bulk cooking oil and packaged cooking oil is inelastic, income elasticity, namely per capita income is inelastic, cross elasticity, namely the population is inferior elastic and the price of chicken eggs is inelastic. Keywords: Cooking Oil Price, Population, Income, Chicken Egg Price, Demand Elasticity